Pattern of Red Cell Count and Red Cell Distribution Width (RDW %) in Beta Thalassaemia Trait in Adults (Bangladesh Journal of Medical Biochemistry, 2018)
Microcytic hypochromic anemia is one of the commonest hematological abnormalities in Bangladeshi population. Iron deficiency anemia and beta thalassemia traits are the most frequent causes of microcytic hypochromic anemia which are sometimes difficult to differentiate clinically and by routine laboratory examinations due to similar blood picture. To differentiate between patients of beta thalassemia trait and iron deficiency anemia, physicians need a group of investigations including peripheral blood film, estimation of HbA2, serum ferritin, serum iron, total iron binding capacity and transferrin saturation. But these tests are relatively expensive, time consuming and need sophisticated techniques. The aim of this study was to evaluate the pattern of red cell count and RDW-CV (%) in beta thalassemia trait in adults and thereby determine the role of these parameters in differentiation between patients of beta thalassemia trait and iron deficiency anaemia. In this study 50 confirmed cases of beta thalassemia trait aged 18 to 60 years, both male and female were included as cases and 50 age- and sex-matched iron deficiency subjects were included as control. RBC count and RDW-CV (%) were measured by an electronic cell counter device. The present study revealed that RBC count was higher in patients with beta thalassemia trait than that in iron deficiency anemia and RDW-CV(%) was significantly higher in patients with iron deficiency anemia than that in beta thalassemia trait.Bangladesh J Med Biochem 2016; 9(1): 31-35